2019
DOI: 10.4236/abb.2019.104006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wild Marjoram (<i>Origanum vulgare</i>) Plant Extracts on Capacitation of Sheep Spermatozoa <i>in Vitro</i>

Abstract: The purpose of this study was to evaluate the effect of the addition of Origanum vulgare extract to in vitro capacitation sperm medium (IVCSM). This study investigated the antioxidant and antimicrobial effects of O. vulgare extracts at different concentrations (0.3, 0.6, 1.2 μg/ml and 25.0, 50.0, 100.0 μg/ml, respectively) in IVCSM. Significant enhancements in semen quality parameters such as total motility, live and live capacitated sperm were found when O. vulgare extract was added as an antioxidant source (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…This study result finding broadly supports the work of other studies in this area linking motility with source of energy and production of ATP which our result showed increased significantly in the general and progressive motility in addition of aqueoussemen extender as showed in Figure (1 and 2). Moreover, the figures illustrated the superiorityof G1 significantly among all groups, This study supports evidence from previous observations (Alenezy et al, 2019;Asadzadeh et al, 2021 andEl-Harairy et al, 2018) uses of natural source of material in the extender of semen for chilling and cryopreservation of the bull sperm, in the seam area the current study found that used of vitamins are promote and increased sperm parameter (general and progressive motility) is support our result (Espina et al, 2021). Also the season in Iraq had a significant effect upon animal testis specially the summer season which show the lowest reproductive activity (Ibrahim and Zaid, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This study result finding broadly supports the work of other studies in this area linking motility with source of energy and production of ATP which our result showed increased significantly in the general and progressive motility in addition of aqueoussemen extender as showed in Figure (1 and 2). Moreover, the figures illustrated the superiorityof G1 significantly among all groups, This study supports evidence from previous observations (Alenezy et al, 2019;Asadzadeh et al, 2021 andEl-Harairy et al, 2018) uses of natural source of material in the extender of semen for chilling and cryopreservation of the bull sperm, in the seam area the current study found that used of vitamins are promote and increased sperm parameter (general and progressive motility) is support our result (Espina et al, 2021). Also the season in Iraq had a significant effect upon animal testis specially the summer season which show the lowest reproductive activity (Ibrahim and Zaid, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In vitro studies on quality and membrane integrity of spermatozoa show that the extract of this plant, due to its phenolic compounds such as gallic acid, rosmarinic acid and quercetin, has the ability to increase the shelf life of cryopreserved Holstein bull spermatozoa following freeze‐thawing process (Daghigh Kia, Farhadi, Ashrafi, & Mehdipour, 2016). In a similar study on sheep, the extract of O. vulgare (100 μg/ml) increases capacitation and sperm parameters of sheep spermatozoa in vitro (Alenezy, Barakat, & Al Musayeib, 2019). Origanum vulgare as a dietary supplement (1,000 ppm/day) improves the reproductive hormones and protects the sperm DNA and membrane against oxidative damage and fertilising capacity in vitro models on frozen sows and boar spermatozoa (Amrik & Bilkei, 2004).…”
Section: Introductionmentioning
confidence: 87%
“…However, during liquid storage, the accumulation of reactive oxygen species (ROS) and the oxidation of sperm plasma membrane cause changes in the spermatozoa and decrease the sperm quality and fertility (Allai et al, 2018; Saha et al, 2022). To avoid such negative effects, the inclusion of antioxidants in extenders can minimize the negative effect of ROS and maintain sperm quality after liquid storage (Alenezy et al, 2019). Recently, the protective effect of natural antioxidants on sperm has been largely discussed (Ajuogu et al, 2020; Allai et al, 2018; Laoung‐on et al, 2022; Ros‐Santaella & Pintus, 2021).…”
Section: Introductionmentioning
confidence: 99%